(untitled) (Journal of Pedagogical Inventions and Practices, 2023)
And citizenship is a conscious observance of legal and moral standards, and a certain citizenship is a conscious observance of legal and moral standards, a certain article indicates that legal culture, the formation of legal consciousness in pre-school adults is one of the pressing issues. Preschool educational institution provides recommendations for the formation of legal literacy in educators.